Student Centered Learning – An Approach to Fostering Democracy in Schools - Jacobs, George; Power, Michael A. (Widya Mandala Catholic University Surabaya, 2016)
After an opening anecdote about a well-functioning small group of students, the article discusses concepts related to democracy. Next, the article defines student centered learning (SCL) and some SCL elements, linking these elements to concepts in democracy. The following section offers various means of implementing SCL. Subsequently, the article looks at issues raised about the use of SCL. To conclude the article, the authors maintain that SCL not only promotes learning but that SCL also fosters democracy